Bio‐Inspired High‐Performance and Recyclable Cross‐Linked Polymers. (17th July 2013) - Yu, Shen; Zhang, Rongchun; Wu, Qiang; Chen, Tiehong; Sun, Pingchuan
<x xml:space="preserve">Abstract</x> Bio‐inspired molecular design and synthesis of high‐performance and recyclable cross‐linked polymers is reported. Reversible cross‐links between hard segments are incorporated into linear segmented polyurethane via Diels‐Alder reaction between maleimide pendant group and furan cross‐linker. The materials form hierarchical structure and exhibit excellent properties with high stiffness, strength and toughness, and can be easily thermally reshaped and re‐mended.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>